Regio‐ and Stereoselective Thianthrenation of Olefins To Access Versatile Alkenyl Electrophiles. (3rd February 2020) - Chen, Junting; Li, Jiakun; Plutschack, Matthew B.; Berger, Florian; Ritter, Tobias
Abstract: Herein, we report a regioselective alkenyl electrophile synthesis from unactivated olefins that is based on a direct and regioselective C−H thianthrenation reaction. The selectivity is proposed to arise from an unusual inverse‐electron‐demand hetero‐Diels–Alder reaction. The alkenyl sulfonium salts can serve as electrophiles in palladium‐ and ruthenium‐catalyzed cross‐coupling reactions to make alkenyl C−C, C−Cl, C−Br, and C−SCF3 bonds with stereoretention. Abstract : Die regioselektive Synthese Sulfonium‐basierter Alkenyl‐Elektrophile gelang durch die direkte C‐H‐Funktionalisierung einfacher Olefine. Die Alkenylsulfoniumsalze können in Palladium‐katalysierten Kreuzkupplungen und Ruthenium‐katalysierten (Pseudo)Halogenierungen eingesetzt werden.